2014
DOI: 10.3892/ijmm.2014.1631
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genes causing hypertension and stroke in spontaneously hypertensive rats: Gene expression profiles in the brain

Abstract: Abstract. Spontaneously hypertensive rats (SHR) and strokeprone SHR (SHRSP) are frequently used as rat models not only of essential hypertension and stroke, but also of attention-deficit hyperactivity disorder (ADHD). Normotensive Wistar-Kyoto rats (WKY) are used as the control rats in these cases. An increasing number of studies has demonstrated the critical role of the central nervous system in the development and maintenance of hypertension. In a previous study, we analyzed the gene expression profiles in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 52 publications
1
16
0
1
Order By: Relevance
“…Gene chip technology and data analysis has been successfully applied in many fields, such as clinical diagnosis, medication guide, drug screening (40), as well as basic medicine (41,42) (expression profiling studies, gene mutation studies and gene component type and sequencing). Gene chip technology is able to analyze a high content of information, in a high-throughput manner, and is rapid and accurate (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene chip technology and data analysis has been successfully applied in many fields, such as clinical diagnosis, medication guide, drug screening (40), as well as basic medicine (41,42) (expression profiling studies, gene mutation studies and gene component type and sequencing). Gene chip technology is able to analyze a high content of information, in a high-throughput manner, and is rapid and accurate (42).…”
Section: Discussionmentioning
confidence: 99%
“…Gene chip technology and data analysis has been successfully applied in many fields, such as clinical diagnosis, medication guide, drug screening (40), as well as basic medicine (41,42) (expression profiling studies, gene mutation studies and gene component type and sequencing). Gene chip technology is able to analyze a high content of information, in a high-throughput manner, and is rapid and accurate (42). In addition, microarray and bioinformatics are complementary to Gene chip technology that were developed to be able to rapidly obtain large amounts of genetic information; they can provide the necessary database for bioinformatics research, while data analysis of gene chips also greatly depends on bioinformatics.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on potential target genes that are involved processes with known functional impact on development and maintenance of hypertension. We developed a list of 144 potential target transcripts that are associated with AT1R signaling through Pkc, CamkII, Mapk, and Pi3k pathways, immediate early genes (e.g., Fos, Egr1, Egr2, Egr3, Jun, Junb), and ion channels and transporters, guided by our previous studies (27,34,39,40,42,51,53,54), as well as genes relevant to inflammatory pathways shown to affect blood pressure regulation, including interleukins, chemokines, and leukotrienes (19,52,60). Several of these pathways are enriched in astrocytes (e.g., inflammatory processes) compared with neurons (e.g., ion channels) compared with endothelial cells (e.g., junctional proteins), whereas the transcriptional regulators and signaling pathways may be common to all cell types (38).…”
Section: Resultsmentioning
confidence: 99%
“…Что касается ингибирования АСЕ, которое не привело к снижению АД, то этот результат может быть связан с развитыми компенсаторными реакциями, возникающими в ответ на ингибирование ACE у крыс НИСАГ, а именно с активацией АСЕ-независимых механизмов генерации Ang II. К таковым можно отнести конверсию Ang I в Ang II химазой, обнаруженной в тканях мозга многих млекопитающих, в том числе гипертензивных крыс SHR (Yoshida et al, 2014). В результате такого альтернативного пути может генерироваться достаточное количество Ang II для стимуляции рецепторов AT1A и поддержания АД на повышенном у гипертензивных крыс уровне.…”
Section: результаты и обсуждениеunclassified